High-strength anti-freezing moisturizing eutectic gel as well as preparation method and application thereof

Through the method of ultraviolet light-induced polymerization, high-strength anti-freeze-moisturized eutectic gel is prepared using deep eutectic solvents, xanthan gums, conductive fillers, crosslinking agents and initiators, which solves the problems of complex processes and poor mechanical strength of the existing eutectic gels, and achieves high-strength, wide temperature range and large-scale production eutectic gels.

CN119798540AActive Publication Date: 2025-04-11ANHUI UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510063720.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-11
Estimated Expiration
2045-01-15

AI Technical Summary

Technical Problem

The existing eutectic gels have complex processes, so they need to accurately control the proportion and conditions of raw materials. They often rely on thermal polymerization, take a long time, have high requirements for equipment, and hinder large-scale production; their mechanical strength is poor, they are difficult to withstand large external forces, and their stability is easily disturbed by environmental factors such as temperature and humidity.

Method used

Deep eutectic solvents, xanthan gums, conductive fillers, crosslinking agents and initiators are used to induce polymerization through ultraviolet light to obtain high-intensity anti-freeze-retaining eutectic gels. The process is simple, the equipment requirements are low, and it is suitable for large-scale production.

Benefits of technology

The obtained eutectic gel has excellent sensing and mechanical properties, and can withstand various deformations such as stretching and twisting without easy damage. Its application range is from -35℃ to 95℃, and its process is relatively safe and suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798540A_ABST
    Figure CN119798540A_ABST
Patent Text Reader

Abstract

The invention relates to high-strength anti-freezing moisturizing eutectic gel and a preparation method and application thereof.The preparation method comprises the following steps that sodium carboxymethyl cellulose and aniline monomers are subjected to in-situ polymerization, a polymerization product is subjected to aftertreatment, and conductive filler is obtained; the preparation method comprises the following steps: mixing a hydrogen bond acceptor and a hydrogen bond donor, heating and stirring until a clear and transparent solution is obtained, and cooling to room temperature to obtain a deep eutectic solvent; adding xanthan gum and the conductive filler into the deep eutectic solvent, and heating and stirring to obtain dispersion liquid; and adding a cross-linking agent and an initiator into the dispersion liquid, and carrying out polymerization initiated by ultraviolet light to obtain the high-strength anti-freezing moisturizing eutectic gel. The eutectic gel is composed of the deep eutectic solvent, the xanthan gum, the conductive filler, the cross-linking agent and the initiator, the eutectic gel is obtained after ultraviolet light initiation, the process is simple, the requirement for equipment is low, the eutectic gel is suitable for large-scale production, and the prepared eutectic gel has excellent sensing performance and mechanical performance and is not prone to damage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of functional polymer materials and flexible wearable electronic technology, and in particular to a high-strength antifreeze and moisturizing eutectic gel and a preparation method and application thereof. Background Art

[0002] Flexible and stretchable sensors have attracted great interest due to their wide applications in wearable devices, human-computer interaction, intelligent robots, electronic skin, and real-time healthcare monitoring. In order to further meet the increasingly complex and versatile requirements of intelligent sensing devices, many efforts have been made to design and produce high-performance and multifunctional electronic sensing materials. Conventional stretchable sensors can achieve their stretchability by bending into different shapes or structures. These sensors have the advantages of high conductivity, but their poor mechanical durability and bottleneck problems in extreme environments limit their application in various fields.

[0003] According to the conductive mechanism, flexible and stretchable sensor conductors can be divided into electronic conductors and ionic conductors, which use electrons and ions as charge carriers, respectively. Electronic conductors lose conductivity and sensing ability due to the separation or breakage of conductive fillers when they are deformed greatly. Ionic conductors usually have higher stretchability and flexibility and can maintain flexibility under large strains. Conductive hydrogels have played an important role in the field of flexible electronics due to their excellent conductivity, flexibility, biocompatibility, and stimulus responsiveness of electrical signals. However, traditional hydrogels using pure water as solvents tend to freeze at sub-zero temperatures and dehydrate in arid environments, which severely limits the application range of the prepared devices. Compared with hydrogels, ionic gels have the characteristics of low volatility, wide electrochemical stability window, and low saturated vapor pressure, providing an ideal solution to solve the instability of hydrogels. However, most ionic liquids are expensive, complex to synthesize, and toxic, making them difficult to be used on a large scale in the field of wearable sensors.

[0004] Eutectic gel has the advantages of traditional ion gel, and its preparation cost is lower than ion gel, and it is non-toxic and harmless. These advantages make it have great application potential in the field of flexible sensors. However, the process of most existing eutectic gels is complicated, requiring precise control of the proportion and conditions of raw materials, and often relying on thermal polymerization, which is time-consuming and requires high equipment requirements, hindering large-scale production; in terms of performance, the mechanical strength is poor, it is difficult to withstand large external forces, and the stability is easily affected by environmental factors such as temperature and humidity. These defects have seriously affected the widespread application and development of eutectic gels. Summary of the invention

[0005] Based on this, the purpose of the present invention is to provide a high-strength antifreeze and moisturizing eutectic gel and its preparation method and application, which is composed of a deep eutectic solvent, xanthan gum, a conductive filler, a cross-linking agent and an initiator. The eutectic gel is obtained after ultraviolet light initiation. The process is simple, the equipment requirements are low, and it is suitable for large-scale production. The prepared eutectic gel has excellent sensing and mechanical properties and is not easy to damage.

[0006] To achieve the above object, the present invention adopts the following technical solutions: The present invention first provides a method for preparing a high-strength antifreeze and moisturizing eutectic gel, which comprises the following steps: S1. After in-situ polymerization of sodium carboxymethyl cellulose and aniline monomer, the polymerization product is post-treated to obtain a conductive filler CMC-PANI; S2. mixing the hydrogen bond acceptor and the hydrogen bond donor, heating and stirring until a clear and transparent solution is obtained, and cooling to room temperature to obtain a deep eutectic solvent; S3. Add xanthan gum and the conductive filler obtained in step S1 to the deep eutectic solvent obtained in step S2, heat and stir to obtain a dispersion; add a crosslinking agent and an initiator to the dispersion, initiate polymerization via ultraviolet light, and obtain a high-strength antifreeze and moisturizing eutectic gel.

[0007] As a further improvement of the above scheme of the present invention, in step S1, the in-situ polymerization method is: dissolving sodium carboxymethyl cellulose in deionized water, adding aniline monomer, hydrochloric acid and ammonium persulfate, and stirring at 0°C for 12-24h; the dosage ratio of the sodium carboxymethyl cellulose, deionized water, aniline monomer, hydrochloric acid and ammonium persulfate is 0.4:40:(0.37-1.85):4.24:(0.91-4.55).

[0008] As a further improvement of the above scheme of the present invention, in step S1, the post-treatment includes: centrifuging the polymer product, washing, dialyzing, and drying.

[0009] As a further improvement of the above scheme of the present invention, the centrifugal speed is 8000-12000 rpm; the washing is performed by alternately washing with deionized water and ethanol for 2-3 times; the dialysis molecular weight cutoff is 3500Da; and the drying is performed at 60-80°C for 6-12h.

[0010] As a further improvement of the above scheme of the present invention, in step S2, the hydrogen bond acceptor is choline chloride, the hydrogen bond donor is ethylene glycol and acrylic acid, and the molar ratio of the choline chloride, the acrylic acid and the ethylene glycol is 1: (1-1.5): (0.5-1); And / or, in step S2, the heating and stirring is stirring at 80-90°C.

[0011] As a further improvement of the above solution of the present invention, in step S3, in the dispersion, the mass ratio of the xanthan gum to the deep eutectic solvent is 0.2-1wt%, and the mass ratio of the conductive filler to the deep eutectic solvent is 0.05-0.2wt%; And / or, in step S3, the heating and stirring is stirring at 80-90°C.

[0012] As a further improvement of the above solution of the present invention, in step S3, the mass ratio of the cross-linking agent to the acrylic acid is 0.1-0.5wt%, and the mass ratio of the initiator to the acrylic acid is 1-5wt%; And / or, in step S3, the cross-linking agent is N-N'-methylenebisacrylamide, bisacrylamide, polyethylene glycol diacrylate or polyethylene glycol dimethacrylate; And / or, in step S3, the initiator is ammonium persulfate or 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

[0013] As a further improvement of the above solution of the present invention, in step S3, the time of ultraviolet light initiating polymerization is 5-10 minutes.

[0014] The present invention also provides a high-strength antifreeze and moisture-retaining eutectic gel, which is prepared by the above-mentioned preparation method.

[0015] The present invention also provides an application of the high-strength antifreeze and moisture-retaining eutectic gel seat conductor as described above in a flexible and stretchable sensor.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention is composed of a deep eutectic solvent, xanthan gum, a conductive filler, a crosslinking agent and an initiator, and a eutectic gel is obtained after being initiated by ultraviolet light. The process is simple, the equipment requirements are low, and it is suitable for large-scale production. The eutectic gel prepared by the present invention has excellent sensing and mechanical properties, can withstand various deformations such as stretching and twisting without being easily damaged, can be used in the range of -35°C-95°C, has a relatively wide operating temperature range, and the preparation process is relatively safe and not prone to danger, has high repeatability, a short preparation cycle, and high safety.

[0017] 2. The deep eutectic solvent of the present invention is composed of choline chloride, acrylic acid and ethylene glycol. The introduction of ethylene glycol not only improves the solubility of xanthan gum, but also improves the antifreeze performance of the eutectic gel; and the addition of the conductive filler CMC-PANI improves the mechanical properties and conductivity of the eutectic gel, which makes it possible to use the eutectic gel in electronic skin, wearable electronic devices, etc., to achieve accurate monitoring of human physiological signals, and open up a new path for health monitoring.

[0018] 3. The flexible strain sensor assembled from the eutectic gel prepared in the present invention shows high sensitivity in monitoring human body movement, is very sensitive to changes in temperature and humidity, can monitor electrical signals, and is suitable for the next generation of wearable and portable strain, temperature and humidity sensor materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 is a tensile break curve diagram of the eutectic gels prepared in Examples 1-5 of the present invention and Comparative Example 1; Figure 2 is a tensile break curve diagram of the eutectic gels prepared in Example 3 and Examples 6-9 of the present invention; Figure 3 is a strain sensing sensitivity curve diagram of the eutectic gel prepared in Example 7 of the present invention; Figure 4 is a curve diagram of relative resistance change of the eutectic gel prepared in Example 7 of the present invention at different strains; Figure 5 is a graph showing the weight retention rate of the eutectic gel prepared in Example 7 of the present invention at different temperatures; Figure 6 This is a comparison diagram of the eutectic gel prepared in Example 7 of the present invention before and after being stored at different temperatures for seven days; Figure 7 is a temperature sensitivity curve diagram of the eutectic gel prepared in Example 7 of the present invention; Figure 8 It is a humidity sensitivity curve diagram of the eutectic gel prepared in Example 7 of the present invention. DETAILED DESCRIPTION

[0020] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0022] Example 1 This embodiment provides a high-strength antifreeze and moisturizing eutectic gel, and the preparation method thereof comprises the following steps: (1) Preparation of deep eutectic solvent: weigh 5.58 g of choline chloride, 3.66 g of acrylic acid and 1.05 g of ethylene glycol, and stir at 90° C. until the solution becomes clear and transparent to obtain a deep eutectic solvent; (2) 0.02 g of xanthan gum was added to the deep eutectic solution obtained in step (1), and the mixture was heated at 90° C. for 2 h to dissolve. Then, 0.018 g of N-N'-methylenebisacrylamide and 0.18 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone were added and mixed evenly to obtain a gel prepolymer solution. The gel prepolymer solution was filled into a polytetrafluoroethylene mold, and the mixture was polymerized by ultraviolet light for 5 min to obtain a eutectic gel DESX. 0.2 .

[0023] Example 2 This example adopts the same implementation method as the example, and the difference from example 1 is that the amount of xanthan gum used in step (2) of this example is 0.04 g, and the eutectic gel DESX is prepared. 0.4 .

[0024] Example 3 This example adopts the same implementation method as the example, and the difference from example 1 is that the amount of xanthan gum used in step (2) of this example is 0.06 g, and the eutectic gel DESX is prepared. 0.6 .

[0025] Example 4 This example adopts the same implementation method as the example, and the difference from example 1 is that the amount of xanthan gum used in step (2) of this example is 0.08 g, and the eutectic gel DESX is prepared. 0.8 .

[0026] Example 5 This example adopts the same implementation method as the example, and the difference from Example 1 is that the amount of xanthan gum used in step (2) of this example is 0.1 g, and the eutectic gel DESX1 is prepared.

[0027] Example 6 This embodiment provides a high-strength antifreeze and moisturizing eutectic gel, and the preparation method thereof comprises the following steps: (1) Preparation of CMC-PANI conductive filler: 0.4 g sodium carboxymethyl cellulose was dissolved in 40 mL deionized water to obtain a sodium carboxymethyl cellulose solution; 1.11 g aniline monomer, 3.6 mL hydrochloric acid and 2.73 g ammonium persulfate were gradually added to the sodium carboxymethyl cellulose solution and stirred at 0 °C for 12 h. The obtained mixture was centrifuged at 12000 rpm for 10 min, washed with deionized water and ethanol alternately for 3 times, dialyzed in a molecular weight cutoff of 3500 Da for 12 h, and dried to obtain CMC-PANI conductive filler.

[0028] (2) Preparation of deep eutectic solvent: Weigh 5.58 g of choline chloride, 3.66 g of acrylic acid and 1.05 g of ethylene glycol, and stir at 90 °C until the solution becomes clear and transparent to obtain a deep eutectic solvent; (3) Take 0.06 g of xanthan gum and 0.005 g of the CMC-PANI conductive filler obtained in step (1) and add them to the deep eutectic solution obtained in step (2), and heat and dissolve them at 90°C for 2 h to obtain a dispersion; add 0.018 g of N-N'methylenebisacrylamide and 0.18 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone to the dispersion, mix well to obtain a gel prepolymer solution; fill the gel prepolymer solution into a polytetrafluoroethylene mold, initiate polymerization by ultraviolet light for 5 min, and obtain a eutectic gel DESX-1.

[0029] Example 7 This example adopts the same implementation method as the example, and the difference from example 1 is that in step (3) of this example, the amount of CMC-PANI conductive filler used is 0.01 g, and the eutectic gel DESX-2 is prepared.

[0030] Example 8 This example adopts the same implementation method as the example, and the difference from example 1 is that in step (3) of this example, the amount of CMC-PANI conductive filler used is 0.015 g, and the eutectic gel DESX-2 is prepared.

[0031] Example 9 This example adopts the same implementation method as the example, and the difference from example 1 is that in step (3) of this example, the amount of CMC-PANI conductive filler used is 0.02 g, and the eutectic gel DESX-4 is prepared.

[0032] Comparative Example 1 This comparative example proposes a eutectic gel, and its preparation method comprises the following steps: (1) Preparation of deep eutectic solvent: weigh 5.58 g of choline chloride, 3.66 g of acrylic acid and 1.05 g of ethylene glycol, and stir at 90° C. until the solution becomes clear and transparent to obtain a deep eutectic solvent; (2) Add 0.018 g of N-N'-methylenebisacrylamide and 0.18 g of 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone to the deep eutectic solution obtained in step (1), mix well to obtain a gel prepolymer solution; fill the gel prepolymer solution into a polytetrafluoroethylene mold, initiate polymerization by ultraviolet light for 5 minutes, and obtain a eutectic gel DES.

[0033] Test Case (1) Study the effect of xanthan gum concentration on the mechanical properties of eutectic gel The eutectic gels prepared in Examples 1-5 and Comparative Example 1 were cut into rectangular samples of 60 mm × 10 mm × 2 mm (length × width × height). The mechanical properties were measured using a universal material testing machine at a stretching rate of 50 mm / min. The stress-strain curves during the stretching process were recorded and analyzed, and then the elongation at break was calculated. The test results are shown in FIG. Figure 1 shown.

[0034] from Figure 1 It can be seen that with the increase of xanthan gum content, the strength of the prepared eutectic gel gradually increases, and its elongation at break first increases and then decreases.

[0035] (2) Based on the concentration of xanthan gum in Example 3, the effect of the content of CMC-PANI conductive filler on the mechanical properties of eutectic gel was investigated. The eutectic gels prepared in Example 3 and Examples 6-9 were cut into rectangular samples of 60 mm×10 mm×2 mm (length×width×height). The mechanical properties were measured using a universal material testing machine at a stretching rate of 50 mm / min. The stress-strain curves during the stretching process were recorded and analyzed, and then the elongation at break was calculated. The test results are shown in FIG. Figure 2 shown.

[0036] from Figure 2 It can be seen that with the increase of CMC-PANI conductive filler content, the strength and elongation at break of the eutectic gel first increase and then decrease.

[0037] (3) The eutectic gel sample prepared in Example 7 was made into a rectangular sample of 40 mm×10 mm×2 mm (length×width×height), and the two ends of the rectangular sample were connected to the electrochemical workstation with wires. The resistance of the rectangular sample was obtained through the electrochemical workstation; the sensitivity was obtained by plotting a series of conductivity response points with strain (%) as the horizontal axis and relative resistance change as the vertical axis into a curve, and the curve was linearly fitted. The slope of the curve was the sensitivity of the strain sensor, and the relative change of resistance was calculated as follows:

[0038] Where R0 and R are the resistances without and with applied strain, respectively.

[0039] By calculating the strain sensitivity of the hydrogel sensor, the sensitivity coefficient (GF) value is obtained as follows:

[0040] Where ε is the strain of the hydrogel (%).

[0041] The results are as follows Figure 3 , Figure 4 As shown. Figure 3 , Figure 4 It can be seen that the eutectic gel prepared in the present application can have a GF value of 1.3 under a strain of 0-400%, and exhibits different relative resistance changes through different strains, and a stable electrical signal can be obtained. The eutectic gel prepared in the present application has good sensing performance.

[0042] (4) Taking the eutectic gel prepared in Example 7 as an example, the anti-drying and anti-freezing properties of the eutectic gel prepared in this application were explored: the eutectic gel samples prepared in Example 7 were placed in a 50°C oven and a -35°C freezer for 15 days, and the changes in their weight and size over time were recorded. The results are as follows: Figure 5 , Figure 6 As shown. Figure 5 , Figure 6 It can be seen that the eutectic gel prepared in the present application can maintain a good weight retention rate at -35°C and 50°C and has good stability. The eutectic gel prepared in the present application is of great significance for further promoting the practical application of conductive hydrogels in the field of flexible electronic materials.

[0043] (5) The eutectic gel sample prepared in Example 7 was made into a rectangular sample of 40 mm × 10 mm × 2 mm (length × width × height). The rectangular sample was placed on a heating plate, and wires were connected to the electrochemical workstation at both ends of the rectangular sample. The rectangular sample was first heated at a first temperature, and the resistance of the rectangular sample was obtained by the electrochemical workstation. When the conductivity value was stable, the temperature was increased and continued to be heated. The above steps were repeated to obtain a relative resistance response curve. A linear fit was made to the curve, and its slope was taken as the temperature sensitivity of the temperature sensor within the temperature range. The results are shown in FIG. Figure 7 As shown. Figure 7 It can be seen that the eutectic gel prepared in the present application has a TCR value of -2.12% / °C at 15-45°C and a TCR value of -0.487% / °C at 45-95°C, and has good temperature sensing performance.

[0044] (6) The eutectic gel sample prepared in Example 7 was made into a rectangular sample of 40 mm × 10 mm × 2 mm (length × width × height), and the two ends of the rectangular sample were connected to the electrochemical workstation with wires. The rectangular sample was placed in an environment with relative humidity of 83%, 75%, 59%, and 43% for testing for 1 hour. The current was recorded twice in the same time period for each humidity test to avoid errors. The relative resistance response curve was obtained, and a linear fit was made to the curve. The slope was taken as the humidity sensitivity of the humidity sensor within the humidity range. The results are shown as follows: Figure 8 As shown. Figure 8It can be seen that the eutectic gel prepared in the present application has a humidity sensitivity of -0.28% / %RH at a humidity of 43%RH-75%RH, and a humidity sensitivity of -0.5% / %RH at a humidity of 75%RH-83%RH, and has good humidity sensing performance.

[0045] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0046] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a high-strength antifreeze and moisturizing eutectic gel, characterized in that: It includes the following steps: S1. After in-situ polymerization of sodium carboxymethyl cellulose and aniline monomer, the polymerization product is post-treated to obtain a conductive filler; S2. mixing the hydrogen bond acceptor and the hydrogen bond donor, heating and stirring until a clear and transparent solution is obtained, and cooling to room temperature to obtain a deep eutectic solvent; S3. Add xanthan gum and the conductive filler obtained in step S1 to the deep eutectic solvent obtained in step S2, heat and stir to obtain a dispersion; add a crosslinking agent and an initiator to the dispersion, initiate polymerization via ultraviolet light, and obtain a high-strength antifreeze and moisturizing eutectic gel.

2. The method for preparing the high-strength antifreeze and moisturizing eutectic gel according to claim 1, characterized in that: In step S1, the in-situ polymerization method is: dissolving sodium carboxymethyl cellulose in deionized water, adding aniline monomer, hydrochloric acid and ammonium persulfate, and stirring at 0°C for 12-24h; the dosage ratio of sodium carboxymethyl cellulose, deionized water, aniline monomer, hydrochloric acid and ammonium persulfate is 0.4:40:(0.37-1.85): 4.24:(0.91-4.55)。 3. The method for preparing the high-strength antifreeze and moisturizing eutectic gel according to claim 1, characterized in that: In step S1, the post-treatment includes: centrifuging the polymer product, washing, dialyzing, and drying.

4. The method for preparing the high-strength antifreeze and moisturizing eutectic gel according to claim 3, characterized in that: The centrifugal speed is 8000-12000 rpm; the washing is performed by using deionized water and ethanol alternately for 2-3 times; the dialysis molecular weight cutoff is 3500Da; and the drying is performed at 60-80°C for 6-12h.

5. The method for preparing the high-strength antifreeze and moisturizing eutectic gel according to claim 1, characterized in that: In step S2, the hydrogen bond acceptor is choline chloride, the hydrogen bond donors are ethylene glycol and acrylic acid, and the molar ratio of the choline chloride, the acrylic acid and the ethylene glycol is 1:(1-1.5):(0.5-1); And / or, in step S2, the heating and stirring is stirring at 80-90°C.

6. The method for preparing the high-strength antifreeze and moisturizing eutectic gel according to claim 1, characterized in that: In step S3, in the dispersion, the mass ratio of the xanthan gum to the deep eutectic solvent is 0.2-1wt%, and the mass ratio of the conductive filler to the deep eutectic solvent is 0.05-0.2wt%; And / or, in step S3, the heating and stirring is stirring at 80-90°C.

7. The method for preparing the high-strength antifreeze and moisturizing eutectic gel according to claim 1, characterized in that: In step S3, the mass ratio of the crosslinking agent to the acrylic acid is 0.1-0.5wt%, and the mass ratio of the initiator to the acrylic acid is 1-5wt%; and / or, in step S3, the cross-linking agent is N-N'-methylenebisacrylamide, bisacrylamide, polyethylene glycol diacrylate or polyethylene glycol dimethacrylate; And / or, in step S3, the initiator is ammonium persulfate or 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.

8. The method for preparing the high-strength antifreeze and moisturizing eutectic gel according to claim 1, characterized in that: In step S3, the ultraviolet light-induced polymerization time is 5-10 minutes.

9. A high-strength antifreeze and moisturizing eutectic gel, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the high-strength antifreeze and moisture-retaining eutectic gel conductor as claimed in claim 9 in a flexible and stretchable sensor.

Citation Information

Patent Citations

  • High-content polyaniline conductive hydrogel material and application thereof

    CN113105654A

  • Preparation method of conductive hydrogel

    CN114605669A

  • Preparation method and application of high-freezing-resistance dual-network eutectic gel

    CN117050342A

  • Preparation method and application of cellulose-based temperature and pressure dual-response type conductive hydrogel

    CN117467082A

  • Production method of cosmetic, preparation method of gel for cosmetics, and method of reducing use amount of polymer thickener blended in cosmetic raw materials

    US20140113976A1